Ekonomi Politik Islam: Pendekatan Maqashid Al-Shari’ah - Ahmad Ubaidillah (JES (Jurnal Ekonomi Syariah), 2018)
The Indonesian nation, which has undergone its independence for more than 70 years, experienced two major changes, namely in 1966 and 1998. 1966 gave birth to the New Order. The New Order period which lasted 32 years with a full orientation to pursue economic growth which was supported by security stability which killed democratic values. We have also gone through the reform era that was rolled out in 1998 which later gave birth to the state order as we feel today. During the 20 years or so of reformation, Indonesia's condition can be said to be more democratic even though it is still procedural which is marked by an election celebration party and post-conflict local election. However, economic orientation and development have almost no fundamental correction, no significant changes. The strategic economic policies taken by the government have not been in favor of the people. Potential economic resources are still held hostage by the interests of foreign countries. Both in the banking sector, insurance, capital markets, state-owned enterprises (BUMN), oil and gas mining and other economic sectors. The government only relies on the amount of economic growth, which does not contribute much to the real economy of the people. As a result, poverty and unemployment rates have not been significantly reduced. The quality of life of the people becomes low. In this paper, the author tries to study the economic growth which is always glorified by the ruling regime in the perspective of Islamic political economy. However, economic policies are inseparable from government political interference. Therefore, questions such as how is the political economy of Islam in view of economic growth amid the high poverty rate of the Indonesian people? Then what is the solution that Islamic political economy can provide in overcoming policies that are deemed not to benefit the people? From the discussion, the writer can provide some things that according to the authors are important to conclude. Islamic political economy is only one area of science that will be built based on the tauhid paradigm. Basically, all existing science needs to be built within the framework of the monotheistic paradigm. The emergence and development of Islamic civilization for more than a thousand years is always based on the Tawhid paradigm. At that time, all science was built on the basis of monotheism. The problem of economic development can be solved by tauhid paradigm. Keywords: Islamic Economic Politics, Maqashid al-Shari’ah Approach